2000
DOI: 10.3758/bf03205548
|View full text |Cite
|
Sign up to set email alerts
|

The effect of segmental order on fricative labeling by children and adults

Abstract: We examined whether children modify their perceptual weighting strategies for speech on the basis of the order of segments within a syllable, as adults do. To this end, fricative-vowel (FV) and vowel-fricative (VF) syllables were constructed with synthetic noises from an If I-to-/s I continuum combined with natural lal and lui portions with transitions appropriate for a preceding or a following IfI or Is/. Stimuli were played in their original order to adults and children (ages of 7 and 5 years) in Experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 68 publications
4
23
0
Order By: Relevance
“…For example, Hazan and Barrett (2000) found that children were more consistent in identification when multiple cues were available compared to when only a single cue was available suggesting that children lack the flexibility to use whatever cue was available. Nittrouer et al (2000) came to a similar conclusion in a study of 5-and 7-year-old children, and Johnson's (2000) observation that even 15-year-olds performed more poorly than adults in speech identification in the presence of noise or reverberation also is consistent with this idea.…”
Section: Flexibility In the Use Of Acoustic Informationsupporting
confidence: 73%
“…For example, Hazan and Barrett (2000) found that children were more consistent in identification when multiple cues were available compared to when only a single cue was available suggesting that children lack the flexibility to use whatever cue was available. Nittrouer et al (2000) came to a similar conclusion in a study of 5-and 7-year-old children, and Johnson's (2000) observation that even 15-year-olds performed more poorly than adults in speech identification in the presence of noise or reverberation also is consistent with this idea.…”
Section: Flexibility In the Use Of Acoustic Informationsupporting
confidence: 73%
“…The kind of evidence that would have supported the first hypothesis would have been evidence that showed that children are less sensitive to changes in static spectral properties than adults, but more sensitive than adults to changes in dynamic spectral properties (i.e., frequency glides). That finding would have supported the absolute-differences hypothesis because children have been found to weight static spectral properties less and dynamic spectral properties more than adults (e.g., Nittrouer, 1992;Nittrouer et al, 2000;Parnell & Amerman, 1978;Siren & Wilcox, 1995). Supporting the second hypothesis would have been evidence that adults are more sensitive to static than they are to dynamic spectral properties, and that children are more sensitive to dynamic than they are to static spectral properties.…”
mentioning
confidence: 93%
“…When formant transitions were added, 4-year-olds' recognition scores improved to 76%. Numerous studies have also shown that young children (i.e., 3−8 years of age) do not weight fricative noise as much as adults in decisions of place for word-initial fricatives, but instead weight formant transitions at voicing onset greatly (e.g., Mayo, Scobbie, Hewlett, & Waters, 2003;Nittrouer, 1992;Nittrouer, Miller, Crowther, & Manhart, 2000;Siren & Wilcox, 1995).…”
mentioning
confidence: 99%
“…Although infants begin to become perceptually tuned to the characteristics of L1 already in the first year ͑Jusczyk, 1997; Kuhl et al, 1992;Werker and Tees, 1984͒, this process ultimately takes significant time to develop to adultlike perception ͑e.g., Morrongiello et al, 1984;Nittrouer et al, 1998;Nittrouer et al, 2000;Nittrouer, 2004;Parnell and Amerman, 1978͒. Specifically, children appear to apply different weightings to acoustic dimensions in perceiving L1 speech categories ͑Hazan and Barrett, 2000; Mayo and Turk, 2004;Nittrouer, 2004͒.…”
Section: Introductionmentioning
confidence: 99%